Growing up Pedro - Tavares, Matt (Candlewick Press, 2015)
Before Pedro Martínez pitched the Red Sox to a World Series championship, before he was named to the All-Star team eight times, before he won the Cy Young Award three times, he was a kid from a place called Manoguayabo in the Dominican Republic. Pedro loved baseball more than anything, and his older brother Ramón was the best pitcher he'd ever seen. He dreamed of the day he and his brother could play together in the major leagues. This is the story of how that dream came true.--